Morphological and Genetic Analysis of Four Color Morphs of Bean Leaf Beetle. Issue 2 (6th April 2018) - Tiroesele, Bamphitlhi; Skoda, Steven R; Hunt, Thomas E; Lee, Donald J; Ullah, Muhammad Irfan; Molina-Ochoa, Jaime; Foster, John E
Abstract: Bean leaf beetle (BLB), Cerotoma trifurcata (Forster; Coleoptera: Chrysomelidae), exhibits considerable color variation but little is known about the underlying genetic structure and gene flow among color phenotypes. Genetic and morphological variation among four color phenotypes—green with spots (G+S), green without spots (G-S), red with spots (R+S) and red without spots (R-S)—were analyzed using amplified fragment length polymorphisms (AFLP) and morphometrics, respectively. AFLP generated 175 markers that showed ≥80% polymorphism. Analysis of molecular variance (AMOVA) indicated that genetic variation was greatest within phenotypes (82.6–84.0%); gene flow among the four phenotypes was relatively high (Nm = 3.82). The dendrogram and STRUCTURE analysis indicated some population divergence of G-S from the other phenotypes. Morphological parameters were similar among phenotypes except that R+S showed significant differences in weight and body-length. Canonical variables 1 and 2, based on average morphometric characters, accounted for 98% of the total variation; some divergence was indicated between G+S and R+S from each other and from the G-S/R-S BLB color morphs. The pattern of genetic variation indicated potential divergence of G-S and G+S from each other and from R-S and R+S. Although these results indicate that the four different color morphs are not genetically or reproductively isolated, there is some genetic differentiation/structure and morphological dissimilarity suggesting weak/incomplete isolation.